Earth observation, open data and machine learning for near real time threat monitoring of vulnerable plant species - Burra, Dharani Dhar; Barua, M.A.; Palao, Leo K.; Reymondin, Louis (International Center for Tropical Agriculture, 2018)
The IUCN data base lists several plant species whose existence is currently threatened by human activities and climatic extremes. Here we report a methodology that monitors threat status of these species in near real time, by deriving data from multiple open data sources, by linking them via a machine learning analytical framework, with interpretations facilitated by a web based geospatial visualization framework.